E-Learning System Design using Software Requirement Specification (SRS) Case Study: Unhar Medan - Indah Sari Daulay; Edy Rahman Syahputra; Septiana Dewi Andriana (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2022)
The development of science, especially in the use of the internet is increasing, in the world of internet education it is used as a remote teaching and learning process using electronic devices called E-Learning. The process of developing E-learning needs to be carried out considering the need for current technological developments, learning is limited due to the pandemic situation which does not allow face-to-face learning but with E-Learning learning can be accessed anywhere and anytime. Implementation of eLearning Universitas Harapan Medan has not been optimally implemented. To meet E-learning standards, it is generally necessary to design specifications in building E-learning. The application of the Software Requirement Specification (SRS) is one way to detail various documents that will explain the various requirements that must be met by an E-learning software. The design of the E-learning system using the Software Requirement Specification (SRS) can facilitate the learning process in E-learning with a system that suits the needs of the user.